Pemetaan Cara Pengembangan Disiplin Anak Usia 5-6 Tahun di Kecamatan Wanasaba Kabupaten Lombok Timur Tahun 2021 - Baedatul Izzah; I Nyoman Suarta; Nurhasanah Nurhasanah; Ika Rachmayani (Indonesian Journal of Elementary and Childhood Education, 2022)
The purpose of this study is to map out how to develop discipline for children aged 5-6 years in Wanasaba District, East Lombok Regency in 2021. This type of research is survey research. The sampling technique in this research is random sampling, with a population of 176 teachers so that the sample taken is 18 teachers who teach in Group B, with the data collection method, namely survey. The data analysis used in this research is a quantitative descriptive approach. The results of the acquisition of research percentages are as follows: the application of regulations which have a total percentage of 69%, the application of punishments is 38.23% and the application of rewards is 57.03%. Based on the percentage results that have been obtained, it can be concluded that all applications of how to develop children's discipline are applied by group B teachers, but the majority of group B teachers in Wanasaba District, East Lombok Regency, are more likely to use the application of regulations, because the application of regulations contributes more in developing discipline for children aged 5-6 years, with the highest percentage gain of 69%.